Emergency risk assessment and rescue of groundwater pollution caused by mining based on 5G network - Zhang, Jiandong (Journal of Environmental Engineering and Landscape Management, 2025)
Recently, heavy metal pollution of soil, land degradation and groundwater pollution generated due to the lack of supporting environmental protection measure, which not only endanger human health, but also affect the sustainable development of mining industry. In order to avoid groundwater pollution, and improve risk assessment and rescue levels of underground water pollution, and a wireless remote emergency risk assessment and rescue system based on 5G core network is constructed, and emergency risk assessment model of groundwater pollution caused by mining is designed. The types of ground water pollution are analyzed. The emergency risk assessment of groundwater pollution is carried out, and the evaluation method of groundwater pollution is designed. A data mining algorithm is designed for optimizing 5G communication network. Taking groundwater in a mining area as the research object, 15 heavy metal indexes of 12 monitoring wells in the mining area were monitored and analyzed. The results show that proposed emergency risk evaluation and rescue of groundwater pollution caused by mining based on 5G network has better communication performance, indexes of as, Sb, Co, Fe and Mn in underground water exceed the standard. And then 5G core network construction of groundwater pollution emergency risk assessment and rescue concludes user plane function/mobile edge computing (UPF/MEC) sink and independent private network is achieved. A case study is carried out using a coal mine as researching object, results showed that proposed remote emergency risk assessment and rescue of groundwater pollution has less time delay and packet loss rate, therefore proposed emergency risk assessment and rescue of groundwater pollution has better communication performance. Finally, the emergency rescue countermeasures of groundwater pollution are taken according to evaluation results.